Ketiadaan Mata Pelajaran Al-Khat pada Maharah Al Kitabah di Pondok Pesantren Al Ihsan, Labuhan Batu Utara - Isna Bulqis Saragi (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
Calligraphy is usually associated with the word khat, which is a skill, the skill of writing Arabic letters beautifully. Judged by its visual beauty, not by the content or material of the author. Calligraphy is also Arabic writing which has certain rules for making letters and how to connect the letters. Calligraphy has a very important role in writing skills (mahārah al kitābah) because it makes a big contribution to the process of writing Arabic letters. In several educational institutions in Indonesia, calligraphy is placed as a subject, because calligraphy more or less influences students' writing skills, but in several other educational institutions they consider that calligraphy is only limited to beautiful writing or art, so they place calligraphy in the extracurricular section, they argue that The imla' subject alone is sufficient in the process of learning to write Arabic, even though in the process of learning to write Arabic, calligraphy and imla' are two pairs that are really needed and both are related and related. This research discusses the impact of the absence of calligraphy subjects on students' writing skills (mahārah al kitābah), especially at the Al Ihsan Labura Islamic boarding school which places calligraphy as an extracurricular activity only.